EVOLUTION OF PUBLIC MANAGEMENT MODELS: CHALLENGES AND TRANSFORMATIONS (International Seven Journal of Multidisciplinary, 2023)
Public management has evolved over the years to meet the growing demands of society and global challenges. Models such as Results-Based Management (RbM) and New Public Management (NPM) have been adopted to promote greater efficiency, transparency, and improved citizen services. These models aim to decentralize processes, increase administrative flexibility, and encourage public-private partnerships to optimize resources and enhance the quality of public service delivery. Digital transformation, driven by the use of new technologies like artificial intelligence and big data, has also played a crucial role in modernizing public administration, facilitating decision-making, and making services more accessible and efficient. However, significant barriers still exist to the full implementation of these models, such as resistance to change, excessive bureaucracy, and the lack of an innovation-driven organizational culture. Overcoming these limitations requires continuous investment in technological innovation, managerial capacity building, and a cultural shift within public institutions. Research on the evolution of public management models indicates that constant adaptation to new social, economic, and technological realities is essential for building a more effective, inclusive, and people-centered public administration. Therefore, adaptation and innovation are crucial to ensuring that public management models can meet the needs of a constantly changing society, promoting a more agile and efficient government.